Whose Knowledge Counts? The Struggle to Revitalise Indigenous Knowledges in Guatemala - Johanna Bergström (MDPI AG, 2021)
This paper investigates the role of indigenous knowledge in relation to ideas of sustainability focusing on Guatemala. Previous research on environmental engagement and public understanding of science demonstrates the importance of including different perspectives, including traditional forms of knowledges such as for example indigenous knowledges. Environmental governance and management are areas in which indigenous peoples strive towards an acceptance of indigenous knowledge to be placed next to Western scientific knowledge. The struggle concerns the management and control of indigenous territories, but it also concerns the dismantling of a hierarchical understanding of knowledge, which lessens indigenous knowledge about ecosystems and about how to create a good life. Through the revitalization of indigenous knowledge and traditional practices, indigenous communities develop ideas and establishments to find paths towards socioecological balance. This paper studies indigenous groups’ understandings of indigenous knowledge, their struggle to revitalise knowledge and their efforts for it to become validated. It uses decolonial theory in its analysis and raises questions of power structures and hierarchies within academia.